Short-term continuous light exposure induces hippocampal rhythmic and functional alterations: a multi-timepoint metabolomics study - Wu, Xiuxuan; Zhang, Guanyu; Wu, Shuai; Hu, Yuyu; Zhang, Yongqiang; Zhang, Li; Li, Xi; Li, Jun; Yang, Danfeng (Frontiers in Molecular Biosciences, 2026)
IntroductionShort-term continuous light exposure disrupts circadian rhythms and impairs cognitive function, yet its specific effects on dynamic metabolic oscillations within the hippocampus remain unclear.MethodsThis study investigated the impacts of short-term (7-day) continuous light exposure (LL) on hippocampal circadian rhythms, metabolome, and cognition in mice. We established an LL model and utilized behavioral assays, histopathology, qPCR for clock genes, and targeted time-series metabolomics (at ZT0, 6, 12, 18).ResultsOur results showed that LL significantly disrupted the circadian oscillations of core clock genes, induced memory decline, and caused hippocampal neuronal abnormalities and neuroinflammation. Metabolomic analysis uncovered extensive remodeling of circadian metabolite rhythms, with a 56.9% reduction in rhythmic metabolites. We identified eight core rhythm-disrupted metabolites, among which the key inhibitory neurotransmitter GABA exhibited a pronounced phase delay (∼6.4 h) and reduced amplitude. Pathway analysis highlighted vitamin B6 metabolism as a central disrupted pathway.DiscussionThese results illustrate that short-term continuous light exposure induces multi-level perturbations in the hippocampal circadian-metabolic network, with GABA and vitamin B6 metabolism as potential critical nodes linking circadian disruption to cognitive impairment. This study provides novel metabolomic insights and a descriptive foundation for understanding the mechanisms underlying light pollution-associated cognitive deficits.